Data Professionals at Work - Mahadevan, Malathi (Apress, 2018)
Enjoy reading interviews with more than two dozen data professionals to see a picture of what it's like to work in the industry managing and analyzing data, helping you to know what it takes to move from your current expertise into one of the fastest growing areas of technology today. Data is the hottest word of the century, and data professionals are in high demand. You may already be a data professional such as a database administrator or business intelligence analyst. Or you may be one of the many people who want to work as a data professional, and are curious how to get there. Either way, this collection helps you understand how data professionals work, what makes them successful, and what they do to keep up. You'll find interviews in this book with database administrators, database programmers, data architects, business intelligence professionals, and analytics professionals. Interviewees work across industry sectors ranging from healthcare and banking to finance and transportation and beyond. Each chapter illuminates a successful professional at the top of their game, who shares what helped them get to the top, and what skills and attitudes combine to make them successful in their respective fields. Malathi Mahadevan is a senior database consultant and has over 20 years of experience working with data, primarily in Microsoft SQL Server and related technologies. She has worked in many industries, such as healthcare, finance, and consulting, to name a few. She also has been volunteering with the SQL Server community by arranging free training and seminars for the past 15 years, and is a recipient of the PASSion award for being an outstanding volunteer from the Professional Association of SQL Server (PASS). She blogs frequently at the Curious About Data site, and is active on Twitter as @sqlmal. Malathi is a featured blogger on the SQL Server Central site, and has also written several articles for the site.